2014
DOI: 10.2337/dc14-0093
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Intensive Lifestyle Intervention on Use and Cost of Medical Services Among Overweight and Obese Adults With Type 2 Diabetes: The Action for Health in Diabetes

Abstract: OBJECTIVETo assess the relative impact of an intensive lifestyle intervention (ILI) on use and costs of health care within the Look AHEAD trial.RESEARCH DESIGN AND METHODSA total of 5,121 overweight or obese adults with type 2 diabetes were randomly assigned to an ILI that promoted weight loss or to a comparison condition of diabetes support and education (DSE). Use and costs of health-care services were recorded across an average of 10 years.RESULTSILI led to reductions in annual hospitalizations (11%, P = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
143
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 29 publications
12
143
0
1
Order By: Relevance
“…This weight loss was significantly greater than the 0.7% and 3.5% weight loss in DSE at year 1 and the end of intervention, respectively. As noted earlier, the lifestyle intervention had a large number of both short‐term and long‐term health benefits relative to DSE 4, 5, 6, 7, 8, 9, 10. In addition, the lifestyle intervention was associated with a reduction in medical care costs, with a 10% savings related to hospitalizations and a 7% savings in medication costs.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…This weight loss was significantly greater than the 0.7% and 3.5% weight loss in DSE at year 1 and the end of intervention, respectively. As noted earlier, the lifestyle intervention had a large number of both short‐term and long‐term health benefits relative to DSE 4, 5, 6, 7, 8, 9, 10. In addition, the lifestyle intervention was associated with a reduction in medical care costs, with a 10% savings related to hospitalizations and a 7% savings in medication costs.…”
Section: Discussionmentioning
confidence: 74%
“…In addition, the lifestyle intervention was associated with a reduction in medical care costs, with a 10% savings related to hospitalizations and a 7% savings in medication costs. Over 10 years, the ILI led to a mean relative per person cost saving of $5,280 7. Future work, which will incorporate additional follow‐up, will evaluate the overall cost‐effectiveness of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have found that current MRFs are important drivers of future morbidity and mortality among individuals with established CVD in a dose‐response fashion 26, 27, 28. Although studies within and outside the United States have attempted to estimate the incremental healthcare expenditures associated with individual cardiovascular MRFs among those without established CVD,29, 30 no study has detailed the potential economic impact of CVD MRFs on pharmaceutical costs, which remains one of the largest contributors to overall healthcare expenditures.…”
Section: Discussionmentioning
confidence: 99%